Characterization of overcurrent relays using open-loop transient-based test method - Tempra, Florentino A. (2004)
This study characterizes the responses of overcurrent relays when subjected to electrical transients using the open-loop transient-based test method. Computer-generated electrical transients as well as transient currents captured by digital fault recorders were used to test different types and brands of relays. Compared to the relay characteristics obtained from phase-based test method which uses purely sinusoidal current, the transient-based test method shows that the relay can behave in a different way as frequency of injected current and as the amount of harmonics distortion are varied. The transient-based method is very useful for fine-tuning relay settings, investigation of relay miss-operations, evaluation of new relays and in future development of protective relays.